El Museo de Arte Moderno de Bogotá entre 1962 y 1967: apuntes para una historia de los museos de arte en Colombia (Dossier: Historias críticas del arte; diálogos transdisciplinarios e indagaciones sobre la estructuración del campo artístico) - López Rosas, William Alfonso (2018)
This article provides a critical review of the operation of the Museum of Modern Art of Bogotá during the administration of the artist Marta Traba. With that in mind, it reinterprets one of the first institutional narratives on the evolution of this museum, published by Traba in 1966. The review of this narrative provides a critical approach to the vision that the artist had for both the process of providing the museum with an institutional framework and the personal stances she took, as well as the curatorial duties that she performed.